Development of MRI Cervical Screening Model to Get Maximum Image Results - Muttaqin Masykur; Gatot Murti Wibowo; Edy Susanto; Mardiyono Mardiyono; Rasyid Rasyid (Journal Research of Social Science, Economics, and Management, 2023)
Abnormal movement can usually occur in any critically ill patient. However, based on the observations made by the author since attending lectures to working in a hospital today, several routine examinations were found with uncooperative patients due to anxiety, anxiety and fear before undergoing examinations and entering the MRI (gantry) area. The research design was a one group pre-test post-test design. The population was all patients who underwent MRI at the Abdoel Moeloek Hospital in Bandar Lampung, totaling 12 people. The sampling technique used simple random sampling with a sample of 12 people. The research instrument used a DASS (Deperession Anxiety Stress Scale) questionnaire with data processing editing, coding, scoring, tabulating and statistical tests using Wilcoxon with ? < 0.05. From the results of the MRI images performed on patients who had received dhikr the results of the MRI images became clearer and less noise was produced. This was because the patient's anxiety level had decreased slightly and even decreased anxiety with dhikr therapy. With calm from the patient, the process of taking MRI images is faster and the results obtained are much easier to read. This research can be interpreted that there is an effect of dhikr relaxation therapy on anxiety levels in MRI patients